Application of membrane bioreactor in wastewater treatment: A mini review - Zaki, Yasmeen Hafiz; Nour, A. H.; Mohamed, Hybat Salih (IJIRSS, 2018)
Membrane bioreactor (MBR) is credible and promising technology methods for industrial wastewater treatment and recycle it to use in different applications. Today MBR has many domestic and industrial applications and it is popular among the types of conventional treatment methods. The main drawback in the operation of MBR is membrane fouling, that drive to the decrease in permeate flux so need some technique to clean the membrane. In spite of more than a decade of significant advances in improvement of fouling reduction technique, various physical and mechanical methods are still necessary to be improved to limit the membrane fouling problems. In this review, the advantages and disadvantages of membrane bioreactor, fundamental of membrane fouling that is affected by some factors and methods of controlling membrane fouling were discussed.